ChemInform Abstract: Synthesis and Luminescence Properties of Novel Red‐Emitting Phosphor InNbO4:Eu3+ for White‐Light Emitting Diodes. Issue 49 (3rd December 2013) - Tang, A.; Zhang, D. F.; Yang, Liu
Abstract Single phase InNbO4:Eu3+ is prepared by solid state reaction of a stoichiometric mixture of In2O3, Nb2O5, and Eu2O3 (1255 °C, 6 h).